Scalable and Affordable IoT-based Inventory Control with Real-Time Monitoring for Small and Medium Enterprises - Yosephine, Vina Sari; Batara, Marco; Setiawati, Marla (Institute of Research and Community Outreach - Petra Christian University, 2025)
Small and medium enterprises (SMEs) often struggle to adopt advanced inventory management systems due to high implementation costs and infrastructure complexity—barriers that are especially challenging in the context of Industry 4.0. This paper presents a scalable and affordable IoT-based stock monitoring and control system designed for small and medium enterprises. The proposed system integrates low-cost microcontrollers with ultrasonic sensors, enabling real-time stock tracking while reducing hardware expenses and complexity. Unlike existing solutions, it leverages a modular architecture for seamless scalability across different inventory sizes and environments. The system is validated through compliance with the Industry 4.0 Maturity Index and the ISA-95 standard, demonstrating its suitability for digital transformation in SME operations. Performance evaluation shows an accuracy rate exceeding 98% and response times under 10 seconds, ensuring reliable operation under varying environmental conditions. A comparative cost analysis highlights significant savings compared to conventional automated inventory systems. This approach provides an accessible entry point for SMEs seeking to enhance inventory visibility, operational efficiency, and readiness for Industry 4.0 integration.